Analisis Kebijakan Otonomi Daerah dalam Peningkatan Kualitas Pelayanan dalam Tinjauan Islam - Ilhami, Ilhami; Aulia Akhmad; Iammillah, Azmiyatul; Rahmawati, Elmi; Juniasari, Juniasari; Lestari, Leni Ayu; Akbar, M. Jofandio; Najah, Nabila Safinatun; Hafizah, Nanda Nur; Safitri, Nita Octaria; Fauziah, Putri Khafifah; Aprianda, Ridho; Ardian, Rizki; Prasetyo, Tegar; Wardani, Yoshinta Kusuma (Economic Reviews Journal, 2024)
The aim of this research is to analyze the regional autonomy policy to improve the quality of public service in the Islamic perspective. Regional autonomy as a policy of decentralization gives authority to local governments to self-regulate regional affairs, with the aim of improving the efficiency and effectiveness of service to local communities. In Islamic terms, the concept of leadership and public service is strongly based on the principles of justice, trust, and the well-being of the people (maslaha). This study uses a method of literature study used to examine articles published in scientific journals at a particular time to find out how Islamic principles can be applied in the context of regional autonomy policy in Indonesia. Research results show that the implementation of Islamic values in regional autonomy policies can improve the quality of public service by strengthening accountability, transparency, and public participation. Furthermore, the implementation of a policy based on Islamic doctrine can encourage the formation of a government that is more responsive and accountable to the needs and wishes of local communities. The study concludes that there is great potential for achieving better public service through the synergy of regional autonomy policies and Islamic principles.